The Equilibrium Time and Salt Expansion Characteristic of Sulfate Saline Soil upon Cooling - Yanjie Ji; Xu Li; Wei Wang; Li Liu (Advances in Materials Science and Engineering)
The salt expansion disease is severe for the soil containing sodium sulfate in cold regions. This paper carried out one-dimensional salt expansion tests of saline soil, the crystallization test of saturated sodium sulfate solution, and the numerical cooling tests to explore the stability time of the salt expansion test and determine the standard procedure of salt expansion tests. The test results demonstrate that (i) the temperature equilibrium and the crystallization process are almost simultaneously completed in both sulfate saline soil and sulfate solution upon cooling; (ii) referring to the deformation equilibrium standard used in soil consolidation test, an expansion rate of less than 0.02 mm/h is suggested in the saline expansion test; and (iii) the equilibrium time is found to have a quadratic polynomial relationship to sample size and is much shorter under liquid bath conditions than under gas bath conditions. Based on these findings, a standard procedure of the one-dimensional salt expansion test is proposed, in which the test equipment, the test process, the deformation stabilization time of salt expansion, and the data processing method are provided. As the deformation and the temperature are synchronized, the deformation stabilization time of samples with different sizes in different cooling media is recommended.